Disease Stage–Dependent Changes in Cardiac Contractile Performance and Oxygen Utilization Underlie Reduced Myocardial Efficiency in Human Inherited Hypertrophic Cardiomyopathy. (May 2017) - Güçlü, Ahmet; Knaapen, Paul; Harms, Hendrik J.; Parbhudayal, Rahana Y.; Michels, Michelle; Lammertsma, Adriaan A.; van Rossum, Albert C.; Germans, Tjeerd; van der Velden, Jolanda
Abstract : Background—: Reduced myocardial efficiency represents a target for therapy in hypertrophic cardiomyopathy although therapeutic benefit may depend on disease stage. Here, we determined disease stage–dependent changes in myocardial efficiency and effects of myectomy surgery. Methods and Results—: Myocardial external efficiency (MEE) was determined in 27 asymptomatic mutation carriers (genotype positive/phenotype negative), 10 patients with hypertrophic obstructive cardiomyopathy (HOCM), 10 patients with aortic valve stenosis, and 14 healthy individuals using [ 11 C]-acetate positron emission tomography and cardiovascular magnetic resonance imaging. Follow-up measurements were performed in HOCM and aortic valve stenosis patients 4 months after surgery. External work did not differ in HOCM compared with controls, whereas myocardial oxygen consumption was lower in HOCM. Because of a higher cardiac mass, total cardiac oxygen consumption was significantly higher in HOCM than in controls and genotype positive/phenotype negative. MEE was significantly lower in genotype positive/phenotype negative than in controls (28±6% versus 42±6%) and was further decreased in HOCM (22±5%). In contrast to patients with aortic valve stenosis, MEE was not improved in patients with HOCM after surgery, which was explained by opposite changes in the septum (decrease) and lateral (increase) wall. Conclusions—: Different mechanisms underlie reduced MEE at the early and advanced stage of hypertrophic cardiomyopathy. The initial increase and subsequent reduction in myocardial oxygen consumption during disease progression indicates that energy deficiency is a primary mutation-related event, whereas mechanisms secondary to disease remodeling underlie low MEE in HOCM. Our data highlight that the benefit of therapies to improve energetic status of the heart may vary depending on the disease stage and that treatment should be initiated before cardiac remodeling.